The christmas tree farm eaudiobook - Gilmore, Laurie (Dream Harbor, 2024)
From the author of the viral TikTok sensations, The Pumpkin Spice Cafe and The Cinnamon Bun Book Store, comes the No. 1 Sunday Times bestselling grumpy x sunshine Christmas romcom to curl up with this winter! 'A charming break from reality' Publishers Weekly Every book in the Dream Harbor series can be read as a standalone. Kira North hates Christmas. Which is unfortunate since she just bought a Christmas tree farm in a town that's too cute for its own good. Bennett Ellis is on vacation in Dream Harbor trying to take a break from both his life and his constant desire to fix things. But somehow fate finds Ben trapped by a blanket of snow at Kira's farm, and, despite her Grinchiest first impressions, with the glow of the fairy lights twinkling in the trees, and the promise of a warming hot chocolate, maybe, just maybe, these two lost souls will have a Christmas they'll remember forever... The Christmas Tree Farm is a spicy romantic mystery with a HEA guaranteed! Tropes: Grumpy x Sunshine Small Town Forced Proximity One Bed Second Chance Readers have fallen for Laurie Gilmore 'Wonderful story with tears, laughter, mysteries, uncertainty and happiness' ⭐⭐⭐⭐⭐ 'Compelling, cozy and delightful narrative' ⭐⭐⭐⭐⭐ 'A charming small town romance with sizzling chemistry and plenty of spice' ⭐⭐⭐⭐⭐ 'I LOVED THIS SO BAD. The vibes of the small town were immaculate' ⭐⭐⭐⭐⭐ 'This book makes my heart happy!' ⭐⭐⭐⭐⭐ 'The perfect kind of romance for me' ⭐⭐⭐⭐⭐